The bedside assessment practices of speech-language pathologists in adult dysphagia - Vogels, B.; Cartwright, J.; Cocks, Naomi (Taylor & Francis, 2015)
Purpose: The current study aimed to investigate what Australian speech-language pathologists frequently include in their bedside assessments in adult dysphagia, what factors influence these bedside assessments and whether they are consistent with the current evidence base. Method: These aims were achieved via an online questionnaire and a series of semi-structured interviews. In the questionnaire, respondents were asked to rate how frequently they utilized bedside assessment components on a scale of five ranging from never to always. Result: One hundred and forty practicing speech-language pathologists completed the online questionnaire in full. Eight interviews were then conducted. Respondents reported utilizing predominantly motor elements of their oro-motor examination with very few sensory elements being frequently utilized. Five main themes arose from the interviews including the influence of the individual patient and participant, the current evidence base, the participants’ clinical practice and the participants’ workplace. Conclusion: The findings from this research have implications for current clinical and education practices, in particular the impact of education and training and caseload demands on current practice.